Changing Values and Identities in the Post-Communist World (Societies and Political Orders in Transition,, 2018)
This book offers a comparative analysis of value and identity changes in several post-Soviet countries. In light of the tremendous economic, social and political changes in former communist states, the authors compare the values, attitudes and identities of different generations and cultural groups. Based on extensive empirical data, using quantitative and qualitative methods to study complex social identities, this book examines how intergenerational value and identity changes are linked to socio-economic and political development. Topics include the rise of nationalist sentiments, identity formation of ethnic and religious groups and minorities, youth identity formation and intergenerational value conflicts. .